Application of Material Criminal Law in the Decision of Case No. 2531/Pid.Sus/2019 / PN Mdn in the Crime of Carrying and Storing Sharp Weapons - Maswandi, Maswandi (International Asia Of Law and Money Laundering, 2024)
The potential for crime that can arise from the possession or carrying of sharp weapons outside the home is very large so that the existence of emergency laws is maintained with a serious criminal threat. The act of carrying and storing sharp weapons that can be categorized as a criminal offense based on the theory of elements of criminal acts and the emergency law of the Republic of Indonesia number 12 of 1951the research method was to use normative methods. This study was conducted by searching and understanding the literature or information security related to social media and literature research. Application of material criminal law in the decision of Case No. 2531/Pid.Sus / 2019 / PN Mdn is in accordance with the application of the law and meets all the elements of Article 2 Paragraph (1) of Law No.12 emergency year 1951, based on the legal facts revealed at the time of the trial in court took place both witness testimony, testimony of the defendant and the evidence the defendant must account for his actions. The defendant who is considered healthy and performs his actions on the basis of his consciousness and is considered able to account for his actions in accordance with the verdict handed down by the panel of Judges, namely 10 (ten) months imprisonment.